Évolution du potentiel hydrique foliaire et de la conductance stomatique de quatre chênes méditerranéens lors d'une période de dessèchement - Acherar, M; Rambal, S; Lepart, J (Ann. For. Sci., 1991)
Influence of soil drying on leaf water potential and stomatal conductance in four Mediterranean oak species. The water relations and the responses of 2 evergreen Quercus species (Quercus ilex L and Q suber L) and 2 deciduous species (Q afares Pomel and Q faginea Willd) were studied under experimental conditions. Two-yr old seedlings grown in 30-1 pots were subjected to a drying period where stomatal conductance, pre-dawn leaf water potential and minimum leaf water potential were measured. The results show that, for all species, the daily course of stomatal conductance agrees with the patterns proposed by Hinckley et al (1978, 1983). Concurrent with the species responses to short-term variation in water availability, it was found that pre-dawn leaf water potential controlled the maximum daily leaf conductance. There was a strong correlation between pre-dawn leaf potential and maximum daily conductance (gsr max) as described by the reciprocal function gsr max = (-0.47 + 2.61 ψb)-1 for the evergreen oaks and gsr max = (-1.94 + 7.39 ψb)-1 for the deciduous ones. The differences between the 2 groups may partially explain their geographic distributions, and also lead to general questions concerning the mechanisms of water use in the Mediterranean oak species.
Keywords: deciduous; evergreen; mediterranean species; Quercus; Stomatal conductance; water potential; water stress